Effect of Triptolide on retinal ganglion cell survival in an optic nerve crush model - Li, Y-F.; Zou, Y-F.; Chen, X-F.; Zhang, W. (Cellular and Molecular Biology, 2017)
Optic nerve crush model could be used to investigate the mechanism of neuronal survival and axonal regeneration in central nervous system. Triptolide, a Chinese herb extract with anti-inflammatory and immunosuppressive activities, has shown neuron protective functions in nervous system. In this study, we investigated the changes in retinal ganglion cell survival and axonal regeneration after administration of triptolide in optic nerve crush model. Triptolide treatment tended to promote retinal ganglion cell survival rather than optic nerve regeneration as well as inhibit the expression of tumor necrosis factor-Î± and activation of nuclear factor-kappa B. These findings suggested that intraperitoneal injection of triptolide may be an effective treatment for optic nerve injury and this effect was attributed at least in part to its anti-inflammatory actions.